PROFIL KEPATUHAN MINUM OBAT PADA PENDERITA TUBERKULOSIS PARU DI RST DR. REKSODIWIRYO PADANG - Nilas Warlem; Raihana Rustam; Soufni Morawati; Sulistiana Dewi; Tria Oktafrianti (Nusantara Hasana Journal, 2023)
The situation of pulmonary tuberculosis in the world is getting worse, the number of pulmonary TB cases is getting out of control with the number of TB patients who have not been successfully cured. To overcome and control the problem of TB disease it is recommended to use the DOTS (Direcly Observed Treatment Shortcourse) strategy. DOTS or treatment with direct observation. Patient discovery and healing is a major focus of the DOTS strategy. One of the important targets that must be achieved in TB control is to cure 85% of infectious TB cases in the community. Objective: To determine the profile of medication adherence in patients with pulmonary tuberculosis at RST Dr. Reksodiwiryo Padang. The scope of this research is research covering the field of pulmonary disease. This research was conducted at RST Dr. Lung Poli. Reksodiwiryo Padang. The research used in this research is descriptive quantitative with cross sectional design. The population was all pulmonary TB patients who were treated at the pulmonary clinic at RST Dr. Reksodiwiryo Padang in 2019 with 67 samples. Univariate data analysis is presented in the form of frequency distribution and percentage and data processing using the computerized SPSS program. The most were 46-55 years old, namely 14 people (20.9%), the most respondents were male, namely 37 people (55.2%), the most respondents with non-school education were 37 people (55 , 2%), the most respondents were civil servants / private workers, namely 23 people (34.3%) and the most respondents with adherence to taking medication obediently, namely 52 people (77.6%). The most age of pulmonary TB patients is 46-55 years, the most sex is experienced by men, the most education is not going to school, the most occupations are civil servants / private companies and the most obedient to taking medication.